2021
DOI: 10.1016/j.asmr.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Medial Collateral Ligament Release Improves Medial Compartment Access During Knee Arthroscopy

Abstract: Purpose To quantify intraoperative joint space widening afforded by the outside-in, percutaneous release of the medial collateral ligament (MCL) and to evaluate its impact on medial compartment width and functional outcomes at 6-week follow-up for patients undergoing a partial medial meniscectomy without postoperative bracing. Methods Patients with posteromedial meniscus tears and no evidence of ipsilateral knee pathology, undergoing partial medial meniscectomy, were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The most remarkable result of the current study is that while both groups demonstrated an improvement in clinical scores (Lysholm, Tegner, IKDC and VAS) compared to the preoperative period, the improvement was statistically superior in the arthroscopic partial meniscectomy with pie-crusting group compared to the arthroscopic partial meniscectomy group at 24 months postoperatively. In studies focusing on patients exclusively utilising the pie-crusting technique, clinical scores exhibited a notable improvement when compared to preoperative measurements [13,30,31]. Unlike our study, studies comparing patients who underwent the pie-crusting technique with the control group found no statistically significant difference in favour of the control group in any of the clinical outcomes at last follow-ups [6,11,20].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The most remarkable result of the current study is that while both groups demonstrated an improvement in clinical scores (Lysholm, Tegner, IKDC and VAS) compared to the preoperative period, the improvement was statistically superior in the arthroscopic partial meniscectomy with pie-crusting group compared to the arthroscopic partial meniscectomy group at 24 months postoperatively. In studies focusing on patients exclusively utilising the pie-crusting technique, clinical scores exhibited a notable improvement when compared to preoperative measurements [13,30,31]. Unlike our study, studies comparing patients who underwent the pie-crusting technique with the control group found no statistically significant difference in favour of the control group in any of the clinical outcomes at last follow-ups [6,11,20].…”
Section: Discussioncontrasting
confidence: 75%
“…While various techniques aim to improve visualisation and access during arthroscopic surgery, their widespread use is hindered by technical complexity, potential morbidity and limited applicability to specific lesions [3,21,23,25,27]. The percutaneous pie-crusting release of the MCL, has been subsequently adopted by various authors in arthroscopic surgeries [6,11,13,14,20,28,30,31]. Given the lack of consensus and concerns raised by some surgeons about its routine use, the true perioperative effectiveness of this technique needs further examination, as noted by Moran et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous release of the posterior fibers of the medial collateral ligament and/or posterior oblique ligament is performed under valgus tension using a spinal needle to open the medial compartment enough to perform posterior root repair without iatrogenic cartilage damage. 9 A standard diagnostic arthroscopy is performed including the confirmation of an MMPRT without significant osteoarthritis (OA) in the medial compartment ( Fig 1 ). The anterolateral portal is used as the viewing portal during the entire procedure.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Regarding MCL fenestration, recent studies have shown it to be a viable technique that does not lead to residual valgus laxity. 25,26 However, further literature is needed to determine if MCL relaxation improves healing and patient reported outcomes after meniscus repair. With regards to post operative restrictions and rehab, prior literature reviews have shown a lack of high-quality evidence in this area.…”
Section: Accepted Manuscriptmentioning
confidence: 99%